2020
DOI: 10.1007/s41885-020-00073-0
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of COVID-19 Stay at Home Orders: Epidemiologic, Economic, or Political Concerns?

Abstract: What factors affected whether or not a U.S. state governor issued a statewide stay-at-home order in response to the COVID-19 pandemic of early 2020? Once issued, what factors affected the length of this stay-at-home order? Using duration analysis, we test a number of epidemiological, economic, and political factors for their impact on a state governor's decision to ultimately issue, and then terminate, blanket stay-at-home orders across the 50 U.S. states. Results indicate that while epidemiologic and economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Other studies have shown that Democratic governors were more likely to issue stay-at-home orders with longer durations. 4,5 Moreover, decisions by Republican governors in spring 2020 to retract policies, such as the lifting of stay-at-home orders on April 28 in Georgia, 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that Democratic governors were more likely to issue stay-at-home orders with longer durations. 4,5 Moreover, decisions by Republican governors in spring 2020 to retract policies, such as the lifting of stay-at-home orders on April 28 in Georgia, 22…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Moreover, another study found that Democratic governors had longer durations of stay-at-home orders. 5 Further, researchers identified governor Democratic political party affiliation as the most important predictor of state mandates to wear face masks. 6 Although recent studies have examined individual state policies, such as mandates to socially distance, wear masks, and close schools and parks, 3,4,[6][7][8] multiple policies may act together to impact the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Other studies have shown that Democratic governors were more likely to issue stay-at-home orders with longer durations. 4,5 Moreover, decisions by Republican governors in spring 2020 to retract policies, such as the lifting of stay-at-home orders on April 28 in Georgia, 22 may have contributed to increased cases and deaths. Thus, governors’ political affiliation might function as an upstream progenitor of multifaceted policies that, in unison, impact the spread of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Moreover, another study found that Democratic governors had longer durations of stay-athome orders. 5 Further, researchers identified governor Democratic political party affiliation as the most important predictor of state mandates to wear face masks. 6 Although recent studies have examined individual state policies, such as mandates to socially distance, wear masks, and close schools and parks, 3,4,6-8 multiple policies may act in unison to impact the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation